Daily Feed Intake, Energy Intake, Growth Rate and Measures of Dietary Energy Efficiency of Pigs from Four Sire Lines Fed Diets with High or Low Metabolizable and Net Energy Concentrations - Schinckel, A. P. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
A trial was conducted to: i) evaluate the BW growth, energy intakes and energetic efficiency of pigs fed high and low density diets from 27 to 141 kg BW, ii) evaluate sire line and sex differences when fed both diets, and iii) to compare ME to NE as predictor of pig performance. The experiment had a replicated factorial arrangement of treatments including four sire lines, two sexes (2,192 barrows and 2,280 gilts), two dietary energy densities and a light or heavy target BW, 118 and 131.5 kg in replicates 1 to 6 and 127 and 140.6 kg in replicates 7 to 10. Pigs were allocated to a series of low energy (LE, 3.27 Mcal ME/kg) corn-soybean meal based diets with 16% wheat midds or high energy diets (HE, 3.53 to 3.55 Mcal ME/kg) with 4.5 to 4.95% choice white grease. All diets contained 6% DDGS. The HE and LE diets of each of the four phases were formulated to have equal lysine:Mcal ME ratios. Pigs were weighed and pen feed intake (11 or 12 pigs/pen) recorded at 28-d intervals. The barrow and gilt daily feed (DFI), ME (MEI) and NE (NEI) intake data were fitted to a Bridges function of BW. The BW data of each sex were fitted to a generalized Michaelis-Menten function of days of age. ME and NE required for maintenance (Mcal/d) were predicted using functions of BW (0.255 and 0.179 BW^0.60 respectively). Pigs fed LE diets had decreased ADG (915 vs. 945 g/d, p<0.001) than pigs fed HE diets. Overall, DFI was greater (p<0.001) for pigs fed the LE diets (2.62 vs. 2.45 kg/d). However, no diet differences were observed for MEI (8.76 vs. 8.78 Mcal/d, p = 0.49) or NEI (6.39 vs. 6.44 Mcal/d, p = 0.13), thereby indicating that the pigs compensated for the decreased energy content of the diet. Overall ADG:DFI (0.362 vs. 0.377) and ADG:Mcal MEI (0.109 vs. 0.113) was less (p<0.001) for pigs fed LE compared to HE diets. Pigs fed HE diets had 3.6% greater ADG:Mcal MEI above maintenance and only 1.3% greater ADG:Mcal NEI (0.152 versus 0.150), therefore NEI is a more accurate predictor of growth and G:F than MEI. Pigs fed HE diets had 3.4% greater ADG:Mcal MEI and 0.11% greater ADG:NEI above maintenance than pigs fed LE diets, again demonstrating that NEI is a better predictor of pig performance than MEI. Pigs fed LE diets had similar daily NEI and MEI but grew slower and less efficiently on both ME and NE basis than pigs fed HE diets. The data suggest that the midds NE value (2.132 Mcal/kg) was too high for this source or that maintenance was increased for pigs fed LE diets.